It's Not About You, It's About Us: A Black Woman Administrator's Efforts to Disrupt White Fragility in an Urban School. (March 2017) - Patton, Lori D.; Jordan, Jodi L.
This case centers on a Black woman school administrator and efforts to disrupt Whiteness among an urban elementary school teaching staff. The case details the resistance she encounters while encouraging teachers to confront "White fragility" and consider how their fragile perspectives on race and racism shape how they educate Black students. She attempts to incorporate relevant social justice issues, particularly associated with the "Black Lives Matter" campaign into professional development to challenge teachers' deficit thinking. Finally, the case demonstrates oppressive leadership politics driving the (mis)education of racially minoritized students.